Memahami Makna dan Praktik Sholawat Amrik: Living Sholawat di Pesantren Ahlus Shafa Wal Wafa - Nilna Sifaana; Herlina Ekaputri; Aditya Firmansyah (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
This study discusses the practice and meaning of Sholawat Amrik as a living tradition that develops in the Ahlus Shafa wal Wafa Islamic Boarding School, Sidoarjo, East Java. Sholawat Amrik is not only practiced in a series of formal ritual worship, but also is present continuously in the daily lives of students and worshippers, such as before meals, after prayers, in routine recitations, and various other collective spiritual activities. This shows that prayer is understood not just as a verbal reading, but as a religious practice that is alive and integrated with the daily pattern of Islamic boarding schools. This study aims to analyze the role of Sholawat Amrik in the process of internalizing religious values, strengthening spirituality, forming religious habits, and strengthening social relations in the pesantren community. The research approach used is qualitative with phenomenological methods, through participatory observation, in-depth interviews, and documentation studies. Data analysis was carried out by linking the findings to Glock and Stark's theory of religiosity, Charles Duhigg's theory of habit formation, and the concept of tazkiyatun nafs in the Sufism tradition of Imam al-Ghazali. The results of the study show that Sholawat Amrik has theological-spiritual, psychological, and social dimensions that contribute to purification of the soul, inner peace, and community solidarity. This practice forms a sustainable religious habit through a cue–routine–reward pattern, so that it becomes an integral part of the lifestyle of students and can be understood as a sufistic heritage that remains relevant in the modern era.